Coexistence of anxiety sensitivity and psychiatric comorbidities in patients with chronic tinnitus - Gul, Ali İrfan; Aydin, Reha; Simsek, Gulnihal; Saydam, Levent; Ozkiris, Mahmut (Neuropsychiatric disease and treatment, 2015)
Tinnitus refers to the objective or subjective perception of a series of sounds most frequently described as ringing in the ear or within the head itself. Anxiety and depressive disorders frequently accompany this complaint. In this study, we aimed to investigate the presence of psychiatric symptoms and the degree of anxiety sensitivity in patients with chronic tinnitus. Fifty patients with chronic tinnitus who had been followed up for at least 6 months or longer were enrolled in this study. All subjects completed the Anxiety Sensitivity Index-3 (ASI-3), Stait-Trait Anxiety Inventory (STAI), and Symptom Check List-90-Revised (SCL-90-R) questionnaires. Fifty healthy volunteers were given the same tests and a statistical comparison of the psychometric outcome data was done for subjects with and without chronic tinnitus. Patients with chronic tinnitus demonstrated higher statistically meaningful scores than the healthy group. Comparison between chronic tinnitus group and control group scores showed that patient group has a high rate of statistically significant results than controls; ASI-3, STAI-2, SCL-90-R GSI, SCL-90-R Somatization, SCL-90-R Depression, SCL-90-R Anxiety (z=-8.00, P<0.01), SCL-90-R Phobic Anxiety. Higher scores for anxiety sensitivity and other psychiatric symptoms in patients with chronic tinnitus reflects the prevalence of psychiatric disorders such as depression, anxiety, somatoform disorder, and chronic tinnitus. The finding of more psychiatric comorbidity in patients with chronic tinnitus indicates that planning and follow-up in both otolaryngology and psychiatry is necessary to improve the overall results of treatment.